The Two Meanings of ’āšam in Leviticus 5 - Meyer, Esias E. (Journal for semitics, 2024)
This article explores how the noun ’āšam is used in Leviticus 5 and focuses especially on the argument that the noun has two meanings. A brief look at a number of translations and the way commentators have translated the different occurrences of the noun will support this argument, but many of these commentators do not offer any explanations for why this is so. This article attempts to fill this gap. It is argued that ’āšam has two meanings, one being a general umbrella meaning and one referring to the sacrifice. From a methodological perspective, much of this article consists of a synchronic reading of Leviticus 5, with some engagement with other texts in Leviticus, especially chapter 4. The article also examines the diachronic debates around this chapter and especially around the history of the ’āšam. The author argues that the Priestly author coined an umbrella term for Leviticus 5 because of the more serious nature of the trespasses in this chapter.